2009
DOI: 10.1016/j.ijmedinf.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The unintended consequences of computerized provider order entry: Findings from a mixed methods exploration

Abstract: Objective To describe the foci, activities, methods, and results of a four-year research project identifying the unintended consequences of computerized provider order entry (CPOE). Methods Using a mixed methods approach, we identified and categorized into nine types 380 examples of the unintended consequences of CPOE gleaned from fieldwork data and a conference of experts. We then conducted a national survey in the U.S.A. to discover how hospitals with varying levels of infusion, a measure of CPOE sophistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 29 publications
2
121
0
Order By: Relevance
“…17 Overall, we found that nurses frequently deal with EHR-UCs, particularly those that affect their workflow, involve interruptions, and involve new work. These results are consistent with studies of EHRUCs with physicians 16 but also those identified in a systematic review of nursing studies. 3 In nursing,…”
Section: Content Validity Was High After 2 Rounds Of Revisions and Qusupporting
confidence: 90%
See 1 more Smart Citation
“…17 Overall, we found that nurses frequently deal with EHR-UCs, particularly those that affect their workflow, involve interruptions, and involve new work. These results are consistent with studies of EHRUCs with physicians 16 but also those identified in a systematic review of nursing studies. 3 In nursing,…”
Section: Content Validity Was High After 2 Rounds Of Revisions and Qusupporting
confidence: 90%
“…The twenty new items were merged with the 8 questions asked by Ash and colleagues in previous qualitative work on EHR-UCs, 16 and combined with 12 other new items asking the nurse to identify the frequency with which the EHR-UCs may have threatened patient safety. With two more questions added during the content validity process, this resulted in a total of 42 items.…”
Section: Carrington-gephart Unintended Consequences Of Ehrs Questionnmentioning
confidence: 99%
“…HIT implementation)" [17] and are normally considered to be outcomes that are undesirable and are rarely anticipated [13-15, 17, 18]. What is apparent is that the introduction of HIT such as CPOE, rather than resulting in more effective, efficient and safer care, may result in a greater workload burden for clinicians, and different types of threats to patient safety [14,15,18]. As HIT systems are used in practice they have an impact on clinician workflow, communication patterns and the broader health care team, all of which may lead to outcomes that were not anticipated when those systems were introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence evaluating the effect of introducing HIT systems such as Computerized Physician Order Entry (CPOE) highlight how unintended consequences can occur once such systems are introduced [13][14][15][16][17][18], and the evidence base supporting the effectiveness of CDSS to improve patient outcomes is equivocal [19]. Similarly, the literature on the effects of using quality measures to improve performance at an organizational level highlights the problems that dashboards can introduce, such as incentivizing certain behaviors or outcomes at the expense of others.…”
Section: Introductionmentioning
confidence: 99%
“…These authors performed a usability assessment discovering that when physicians entered medication orders, the system-generated electronic time schedules were ambiguous to nurses. Interestingly, numerous studies are published on CPOE [15][16][17][18][19][20][21][22] a process that involves nurses. However, Weir, Staggers and Phansalkar [23] completed a systematic review of CPOE studies and found that nurses were not a population of interest for studies published in refereed journals.…”
Section: Emars and Patient Safetymentioning
confidence: 99%